The effect of financial literacy, financial self-efficacy, financial technology literacy, and risk perception on stock investment decisions: Millennials preferences - Sunarko, Cahyo; Sutrisno, Sutrisno (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Nowadays, investment has major importance for future contingencies. The millennials are one that currently take over a large number of capital market investors. To advocate optimal and sustainable decision-making in stock investment, it is important to explore the determinants of investment decisions which include financial literacy, financial self-efficacy, and risk perception. The study was conducted to assess the influence of financial literacy, financial self-efficacy, financial technology literacy, and risk perception on stock investment decisions in the millennial generation of Yogyakarta Special Region. The population of this study was millennial stock investors in the D.I. Yogyakarta province. The sample is used with criteria that age in between investing 28–43 years old; namely 115 people. The data was collected via a survey strategy and then analyzed using the SEM-PLS technique. Based on the research findings, it can be concluded that financial literacy has a significant positive effect on stock investment decisions among the millennials in Yogyakarta. Conversely, financial self-efficacy negatively impacts stock investment decisions significantly. Additionally, financial technology literacy also demonstrates a positive and significant influence on stock investment decisions. In contrast, risk perception does not appear to affect stock investment decisions among millennials in Yogyakarta. Theoretical and practical implications are discussed in the last section of this article.